2003
DOI: 10.1124/jpet.103.051789
|View full text |Cite
|
Sign up to set email alerts
|

N-n-Alkylpyridinium Analogs, a Novel Class of Nicotinic Receptor Antagonists: Selective Inhibition of Nicotine-Evoked [3H]Dopamine Overflow from Superfused Rat Striatal Slices

Abstract: Structural simplification of N-n-alkylnicotinium analogs, antagonists at neuronal nicotinic acetylcholine receptors (nAChRs), was achieved by removal of the N-methylpyrrolidino moiety affording N-n-alkylpyridinium analogs with carbon chain lengths of C1 to C20. N-n-Alkylpyridinium analog inhibition of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Nicotine-evoked overflow of [ 3 H]DA (28 Ci/mmol, Perkin Elmer, Boston, MA) from striatal slices preloaded with [ 3 H]DA was determined using a previously published method with minor modifications [57,64,65]. Briefly, striatal slices were prepared using a McIlwain tissue chopper (Mickle Laboratory Engineering Co Ltd, Surrey, England).…”
Section: [ 3 H]da Release Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine-evoked overflow of [ 3 H]DA (28 Ci/mmol, Perkin Elmer, Boston, MA) from striatal slices preloaded with [ 3 H]DA was determined using a previously published method with minor modifications [57,64,65]. Briefly, striatal slices were prepared using a McIlwain tissue chopper (Mickle Laboratory Engineering Co Ltd, Surrey, England).…”
Section: [ 3 H]da Release Assaymentioning
confidence: 99%
“…Native subtypes by convention have an asterisk designation to indicate putative composition [28]. Results show that α-conotoxin MII (α-CtxMII), the Conus snail peptide neurotoxin, as well as small quaternary ammonium molecules, N-npentadecylpyridinium bromide, N-eicosylpyridinium bromide and N,N′-dodecyl-1,12-diylbis-3-picolinium dibromide (bPiDDB), only partially inhibit nicotine-evoked striatal DA release, indicating involvement of more than one population of nAChR subtype [29][30][31][32][33][34]. Studies using β2 knockout mice have shown the involvement of β2-containing nAChRs in nicotine-evoked DA release [31,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…71 Results showing that both the Conus snail peptide neurotoxin, α-conotoxin MII (α-CtxMII), and the small quaternary ammonium molecules, N-n-pentadecylpyridinium bromide (NPDPB), N-neicosylpyridinium bromide (NEcPB), and bis-picoliniumdodecyl bromide (bPiDDB), only partially inhibit nicotineevoked striatal [ 3 H]DA release indicate the involvement of more than one population of nAChR subtype mediating this response. [72][73][74][75][76] Initially, the α3β2* nAChR subtype was suggested to mediate nicotine-evoked striatal DA release, based on the observations that neuronal bungarotoxin and α-CtxMII were selective for the α3β2 subtype in recombinant receptor assay systems [77][78][79] and that nicotine-evoked DA release was sensitive to inhibition by neuronal bungarotoxin and α-CtxMII. 43,72,80 Consistent with the latter results, studies using β2 knockout mice have clearly demonstrated the involvement of β2-containing nAChRs in nicotine-evoked [ 3 H]DA release.…”
Section: E202mentioning
confidence: 99%
“…75,100 Briefly, striata from 2 rats were dissected, pooled, and homogenized in 10 vol of ice-cold Krebs-HEPES buffer (in mM: 20 HEPES, 118 NaCl, 4.8 KCl, 2.5 CaCl 2 , 1.2 MgSO 4 , pH 7.5). Homogenates were incubated at 37°C for 5 minutes, and then centrifuged (27 000g for 20 minutes at 4°C).…”
Section: [ 3 H]nicotine Binding Assaymentioning
confidence: 99%
See 1 more Smart Citation